Evaluation of nitrate pollution, health risk and groundwater vulnerability in agricultural and non-agricultural areas - Shamsuddin, Aida Soraya (2018)
Majority population in Kelantan use shallow private well water for their domestic purposes. However, nitrate can easily contaminate the shallow wells. An agricultural activity has been identified as a major source of groundwater nitrate contamination. Meanwhile, discharge of septic tanks and livestock activities in non-agricultural area also contribute to nitrate contamination which consequently affects human health. Therefore, this study aimed to evaluate nitrate contamination, health risk and groundwater vulnerability in agricultural and non-agricultural areas. This cross-sectional study was conducted from October to December 2015 in Bachok district, Kelantan. Questionnaires were distributed among 300 respondents and their private well waters were analyzed for nitrate and others parameters such as pH, EC, NH4+, TDS, turbidity and salinity. Three substudies have been divided in this study; 1) Groundwater nitrate contamination assessment, 2) Health risk assessment of groundwater nitrate exposure and 3) Groundwater vulnerability assessment. In sub-study 1, nitrate concentrations were compared with the drinking water standard, potential nitrate sources were identified by multivariate analysis, groundwater quality was determined by different indices and distribution of nitrate were illustrated by spatial analysis. In sub-study 2, association of nitrate with perceived health symptoms and associated diseases were determined and health risks were calculated. In sub-study 3, the vulnerability of aquifer was evaluated by DRASTIC model. Based on measurement, nitrate in agricultural area (15.10 ± 15.90 mg/L NO3-N) was significantly higher than non-agricultural area (5.81 ± 5.08 mg/L NO3-N) (Z = -5.83, p < 0.001). About 46.0% and 24.0% samples in agricultural and non-agricultural areas, respectively, exceeded the drinking water quality standard. Principal component analysis (PCA) have identified the groundwater quality in the study area was influenced by natural processes and anthropogenic activities. Hierarchal cluster analysis (HCA) determined Cluster II in agricultural area was heavily contaminated by nitrate, while seawater intrusion was strongly influenced Cluster III in non-agricultural area. Groundwater Quality Index (GWQI) showed all the samples were suitable for drinking purpose. However, based on Nitrate Pollution Index (NPI), 80.7% and 56.0% of samples in agricultural and non-agricultural areas, respectively were polluted with nitrate. In sub-study 2, 21.29% and 18.75% of males and females in agricultural area, respectively had HQ > 1, and only 1.60% (n = 1) females in non-agricultural area had HQ > 1. In sub-study 3, DRASTIC index illustrated 27.14 % of areas fall under low vulnerable zones (159 – 175), 14.50% moderate vulnerable zones (176 – 192) and 58.36% high vulnerable zones (193 – 208). For the modified DRASTIC index, 8.47% of the area laid under low vulnerability (161 – 190), 61.03% moderate vulnerability (191 – 219) and 30.50% high vulnerability (220 – 248). The findings of this study are useful for developing protection alternatives of private well waters to prevent further deterioration of groundwater quality by nitrate and reduce the health risks for local residents. In addition, determination of vulnerable zones can be used to improve the sustainability of the groundwater resources through proper land use management.